PENERAPAN ISAK 35 PADA PONDOK PESANTREN DENA CILENGKRANG - Kurniawan, Sandy; Sudrajat, Ade (Jurnal Sosio dan Humaniora (SOMA), 2024)
DenA Islamic Boarding School is a non-profit organization whose funding sources come from the community and other legal and non-binding sources. Islamic Boarding School accountability for these donations needs to be carried out transparently and reported periodically in the form of financial statements to avoid misuse of funds and increase the credibility of Islamic Boarding School to external parties. Currently, the standard for preparing financial statements that applies to non-profit entities is ISAK 35, but many Islamic Boarding School have not applied it and Islamic Boarding School denA is among them. This research aims to find out how the preparation of financial statements that have been done so far, the research method uses descriptive qualitative methods. Research data obtained through interviews, documentation, and literature study. The results of this study indicate that the denA Islamic Boarding School is still manual in recording and preparing its financial statements and only compiling reports on cash receipts and disbursements. Therefore, the author helps prepare financial statements based on ISAK 35 for the period ending December 31, 2023. The implications of the preparation of this report can help Islamic Boarding School denA in preparing financial reports effectively and efficiently for future periods.